Integrated Virtual Queuing System - Abd Rahman, Danial (IRC, 2020)
Queuing is a very common practice in everyday life, some examples are waiting for turns on a counter, queuing for a seat on restaurant, or even for the service at a bank. This experience is not comfortable for most people because it involves a lot of waiting and wasting valuable time and energy. The feature to inform the waiting customers is much needed because it allows the customer to have a sense of when they will be served. Moreover, customer can attend to other places before getting into queue. However, informing with individuals waiting in a queue manually or verbally has been inefficient and not real-time. There should be a system that can notify the waiting queue number and estimated waiting time for the customers, the system should be updating through a most common device that every people own, which is mobile phone. A waterfall methodology which will be used to execute this project on developing the application. In the end of research, will measure how effective the system would be in regard to the queuing system.